Kinetics of thin polymer film rupture: Model experiments for a better understanding of layer breakups in the multilayer coextrusion process. (4th May 2016) - Zhu, Y.; Bironeau, A.; Restagno, F.; Sollogoub, C.; Miquelard-Garnier, G.
Abstract: We show that the kinetics of bursting of a thin film embedded in another polymer matrix can be well described by a simple equation balancing the viscous and capillary forces. The role of viscosity, interfacial tension and thickness of the layers under static conditions was investigated by adapting a simple model experiment initially designed to study the dewetting of a thin polymer film on another polymer substrate. Kinetics was correlated to instabilities occurring during multilayer coextrusion leading to the break-up of layers below a critical nanometric thickness. The results suggest that shear and elongation forces during the process actually stabilize the layers. Understanding these instabilities is of great interest since this innovative process showed potential to design at an industrial scale macromolecular materials displaying new macroscopic properties, due to interfacial and confinement effects. However, instabilities leading to the breaking of these nanometric layers will alter final properties (optical, gas barrier …). Graphical abstract: Highlights: Kinetics of rupture of thin polymer films heated above Tg were studied. Results for thin films on top of another polymer agree with theoretical predictions. A simple model describes the behavior for thin film within another polymer matrix. Kinetics of rupture is faster than what can be observed in multilayer coextrusion.